A Research Methodology Course for Accountants. - Deskins, James Wesley; Neumann, Frederick L.; Revsine, Lawrence (The Accounting Review, 1970)
The article provides information on an alternative research methodology course for a master's degree in accounting. With the advent of a more generalized business degree at the master's level, the requirement of a master's thesis has become less common. As a result, many master's degree students never have the opportunity of performing an extensive independent research effort under faculty supervision. The problems facing practicing accountants of the future promise to be increasingly complex. A course providing experience in the employment of investigative techniques may assist the future accountant in analyzing these problems and in developing and appraising alternative solutions to them. The illustrative readings are used to add an accounting perspective to the topic being considered. These illustrative articles were selected in an attempt to put the basic ideas into a context more relevant to the student's interest. Hopefully this background will enable the future practitioner to evaluate the research of others. An ancillary benefit may be provided for those students who choose to contribute to the literature. They should have a stronger methodological base for doing so.